2010
DOI: 10.3390/molecules15096140
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Filamentous Fungi to Identify Biocatalysts for Lupeol Biotransformation

Abstract: The goal of the study was to evaluate the ability of filamentous fungi to biotransform the pentacyclic triterpene lupeol. The microbial transformations were carried out in shake flasks in different media. Experiments were also run with control flasks. Samples of each culture were taken every 24 hours, extracted with ethyl acetate, and analyzed by GC-MS. The biotransformation of lupeol by Aspergillus ochraceus and Mucor rouxii afforded two compounds in each culture, which were detected in the cultures developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…20 For lupeol and diploptene, spectral data contributed significantly to their characterization through detection of molecular ions (m/z 426 and m/z 410, respectively) and base peaks (m/z 191 and m/z 218, respectively). 21,22 Besides these, other characteristic fragments are shown in figure 7. Paula et al 14 In the mass spectra of kaur-16-ene, it was observed a molecular ion peak (m/z 272), compatible with the molecular formula C20H32.…”
Section: Resultsmentioning
confidence: 99%
“…20 For lupeol and diploptene, spectral data contributed significantly to their characterization through detection of molecular ions (m/z 426 and m/z 410, respectively) and base peaks (m/z 191 and m/z 218, respectively). 21,22 Besides these, other characteristic fragments are shown in figure 7. Paula et al 14 In the mass spectra of kaur-16-ene, it was observed a molecular ion peak (m/z 272), compatible with the molecular formula C20H32.…”
Section: Resultsmentioning
confidence: 99%
“…Modification of the triterpenoid structure may produce potentially new and interesting derivatives. Synthetic approaches can be used, but biotransformation processes have been used in order to target positions which are more difficult to functionalize using chemical methods (Carvalho et al 2010).…”
Section: R=hmentioning
confidence: 99%
“…Research on production of bioactive compounds through fungi biotransformation had been a hot point in biomedicine field [8][9][10][11][12]. However, to our knowledge, there were very few reports on screening of microorganism of highly efficient biotransformation of dioscin to diosgenin and no reports on direct biotransformation of RDZ, which was simple and more practical.…”
Section: Introductionmentioning
confidence: 99%